Composition, antioxidant and anti-inflammatory activities of different polarity extracts of Artemisia nilagirica collected from hilly areas in the Himalayan terrain of Uttarakhand - Garia, Vaishali; Dubey, Shiv Kumar; Bahuguna, Ananya; Kumar, Ravendra; Prakash, Om; Rawat, Dharmendra Singh (European Journal of Chemistry, 2023)
The plant Artemesia nilagirica, collected from the terrain of the Himalayan region in Uttarakhand, India, was evaluated for its phytochemical composition, antioxidant and anti-inflammatory activities in vitro. The different polarity extracts of the plant were prepared and subjected to GC-MS analysis for their phytochemical composition. Twenty-six compounds were identified in the hexane extract of Artemisia nilagirica that represents 73.30% of the total area. The main compounds were tetracontane (15.21%), heneicosane (6.52%), and phytyl tetradecanoate (5.11%). The methanol extract yielded 26 compounds, accounting for 83.78% of the total compounds detected. The main compounds were palmitic acid (13.25%), alpha-linolenic acid (10.32%), oleamide (9.41%), phytol (8.58%), muco-inositol (7.27%), and neophytadiene (5.05%). The hexane and methanol extracts showed significant metal chelating activity having IC50 values of 2.23±0.01 and 2.41±0.02 µg/mL, respectively, with standard EDTA having an IC50 value of 2.22±0.01 µg/mL. The methanol extract showed a better anti-inflammatory property having an IC50 value of 2.97±0.03 µg/mL compared to the standard diclofenac potassium having an IC50 value of 3.79±0.01 µg/mL. The hexane extract showed better antioxidant activity in terms of metal chelating activity and reducing power activity than the methanol extract. The anti-inflammatory activity of both hexane and methanol extracts showed better results than the standard marketed drug diclofenac potassium. The current study reveals that Artemisia nilagirica plant extracts have potent antioxidant and anti-inflammatory activities. The effective biological compounds of plant extracts, such as phenols and flavonoids, can be potential alternatives to standard pharmaceuticals.